The Mediating Role of Body Self-Concept in the Relationship Between Self-Compassion and Emotional Eating in Individuals with Obesity - Babakhanlou, Ashraf; Babakhanlou, Zahra (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This research aimed to investigate the mediating role of body self-concept in the relationship between self-compassion and emotional eating in individuals with obesity. Materials and Methods: The study employed a cross-sectional correlational design. The population consisted of all individuals with obesity in Tehran in the year 2019, from which 378 participants were selected through convenience sampling in two stages. The study utilized the Emotional Eating Scale (Dutch, 1986), the Self-Compassion Scale (Neff, 2003), and the Body Self-Concept Scale (Marsh, 1996), all of which have acceptable reliability and validity. SPSS-V24 and Lisrel-V8.8 software were used for data analysis. Structural equation modeling was also applied to test the research hypotheses. Findings: The findings indicated that the model had a good fit. Furthermore, the results showed that the structural model of self-compassion on emotional eating, with the mediating role of emotional processing, in individuals with obesity has a significant relationship. Conclusion: Therefore, the findings support the presence of underlying psychological mechanisms in the occurrence of obesity. Accordingly, attention to these variables in prevention and designing more appropriate treatments provides aid to researchers and therapists.